Case Report: Successful treatment of triple primary cancers (lung, stomach, and intestine) using sintilimab combined with chemotherapy and targeted therapy - Zhang, Qi-Qing; Luo, Xin-Xin; Chen, Hua; Wang, Wei; Xie, Yi-Fan; Qiao, Hong-Li; Miao, Hao-Jun; Feng, Zheng-Quan (Frontiers in Immunology, 2025)
This case report presents a rare instance of synchronous multiple primary cancers involving lung adenocarcinoma with bone metastasis, gastric signet-ring cell carcinoma, and rectal cancer. The 64-year-old male patient was treated with a combination of sintilimab, chemotherapy, and targeted therapy. Following a multidisciplinary team consultation, systemic treatment with sintilimab, oxaliplatin, and capecitabine was initiated concurrently while furmonertinib targeted therapy continued. After six cycles, the lung lesions showed significant reduction, while the gastric and intestinal tumors remained stable. The patient transitioned to maintenance therapy and achieved sustained disease control without severe adverse effects. This case highlights the potential of an integrated immunotherapy and chemotherapy approach for treating multiple primary malignancies with distinct pathological origins. report also underscores the need for individualized, biomarker-driven treatment strategies and further research on optimal therapeutic combinations for synchronous multiple primary cancers.